Implementing SAP CRM : the guide for business and technology managers - Kale, Vivek (Boca Raton, Florida : CRC Press, 2015)
This book explains what it means to be a customer-centric and responsive enterprise, and provides a framework for business operations based on customer relationships, rather than the traditional four Ps (product, positioning, price, promotion).
Section 1. Setting the stage -- Section 2. SAP CRM applications -- Section 3. Pre-implementation stage -- Section 4. Implementation stage -- Section 5. Post-implementation stage -- Section 6. SAP CRM implementation and beyond.
Includes bibliographical references and index.
Keywords: CUSTOMERS RELATION -- DATA PROCESSING